THE LEGAL SYSTEM OF THE LIMITED LIABILITY COMPANY IN LIGHT OF RECENT AMENDMENTS - Mohammed Saud Dhannoon (International Journal of Business, Law and Political Science, 2025)
Objective: This research deals with the legal system of the limited liability company in light of the recent legislative amendments to the Iraqi Companies Law No. (21) of 1997. Method: The researcher adopted the descriptive and comparative analytical approach to monitor the development and deficiencies in the legal framework. Results: The research shows the effectiveness of the new amendments in simplifying procedures, enhancing transparency, and protecting rights by analyzing comparative legal texts and reviewing the impact of these amendments in practice. Novelty: The study concludes that the recent amendments have contributed to facilitating the business environment and achieving a better balance between legal flexibility and organizational discipline, but they still need to be further activated through executive regulations and the training of competent administrative and legal cadres.